Estrogen replacement is protective to the effect of in vitro hypoxia on female rabbit bladder and pelvic floor contractile response - Dobberfuhl, Amy D. (Investig Clin Urol, 2020)
PURPOSE: To explore the effect of estrogen replacement on pelvic floor and bladder contractile response to electrical field stimulation, following in vitro hypoxia in an animal model of surgical menopause. MATERIALS AND METHODS: Twelve female adult rabbits were divided into three groups: control, ovariectomy, and ovariectomy with estradiol replacement. At 4 weeks animals were euthanized. Bladder, coccygeus, and pubococcygeus were isolated. Tissues were equilibrated with oxygenated Tyrodes containing glucose and stimulated with electrical field stimulation. Tissues were then stimulated under hypoxic conditions for 1 hour using nitrogenated Tyrodes without glucose. Tissues were then re-oxygenated for 2 hours and stimulated. RESULTS: Pelvic floor required 10 times the stimulation duration (power) to achieve maximum contraction at 2 g baseline tension (10 ms duration) when compared to bladder (1 ms duration). Maximal tension generated was significantly greater for bladder than pelvic floor. Coccygeus and pubococcygeus were significantly less sensitive to the effects of hypoxia and had stable contractile response to field stimulation throughout the hour of hypoxia. Hypoxia resulted in progressive and rapid decline of bladder contractile strength. Following hypoxia, pelvic floor contractile recovery was superior to bladder. Improvement in the contractile response of both bladder and pelvic floor, during the period of post-hypoxia re-oxygenation, was significantly greater in ovariectomy animals treated with estradiol replacement. CONCLUSIONS: Replacement of estradiol at time of ovariectomy reduced oxidative stress on tissue and was protective to the effects of hypoxia on pelvic floor and bladder contractile function.